Double distress: women healthcare providers and moral distress during COVID-19 - Smith, Julia (Nursing ethics, 2023)
Background: COVID-19 pandemic has led to heightened moral distress among healthcare providers. Despite evidence of gendered differences in experiences, there is limited feminist analysis of moral distress.Objectives: To identify types of moral distress among women healthcare providers during the COVID-19 pandemic; to explore how feminist political economy might be integrated into the study of moral distress.Research Design: This research draws on interviews and focus groups, the transcripts of which were analyzed using framework analysis.Research Participants and Context: 88 healthcare providers, based in British Columbia Canada, participated virtually.Ethical Considerations: The study received ethical approval from Simon Fraser University.Findings: Healthcare providers experienced moral dilemmas related to ability to provide quality and compassionate care while maintaining COVID-19 protocols. Moral constraints were exacerbated by staffing shortages and lack of access to PPE. Moral conflicts emerged when women tried to engage decision-makers to improve care, and moral uncertainty resulted from lack of clear and consistent information. At home, women experienced moral constraints related to inability to support children’s education and wellbeing. Moral conflicts related to lack of flexible work environments and moral dilemmas developed between unpaid care responsibilities and COVID-19 risks. Women healthcare providers resisted moral residue and structural constraints by organizing for better working conditions, childcare, and access to PPE, engaging mental health support and drawing on professional pride.Discussion: COVID-19 has led to new and heightened experiences of moral distress among HCP in response to both paid and unpaid care work. While many of the experiences of moral distress at work were not explicitly gendered, implicit gender norms structured moral events. Women HCP had to take it upon themselves to organize, seek out resources, and resist moral residue.Conclusion: A feminist political economy lens illuminates how women healthcare providers faced and resisted a double layering of moral distress during the pandemic.